Experimental and Theoretical Studies of Ultrasonic Velocity in Ternary Liquid Mixtures of Methyl Benzoate, Cyclohexane and Alcohols at Different Temperatures - Muthukrishnan, Umadevi; Ramasamy, Kesavasamy; Rathinasamy, Palani; Nachimuthu Senniappan, Priya (Asian Journal of Chemistry, 2014)
Ultrasonic velocities of ternary liquid mixtures of methyl benzoate and cyclohexane with 1-propanol, 1-butanol, 1-pentanol and 1-hexanol are measured using ultrasonic interferometer at 303, 308 and 313 K over the entire range of composition. Theoretical values of ultrasonic velocity have been evaluated at the three temperatures using Nomoto's relation, ideal mixture relation, impedance relation, Junjie's method, Rao's specific velocity relation and free length theory. Theoretical values are compared with the experimental values and Uexp2/Uimx2 is evaluated for non-ideality in the mixtures. A good agreement has been found between experimental and theoretical values of ultrasonic velocity. The relative applicability of these theories to the present systems has been checked and discussed. The results are explained in terms of molecular interactions occurring in these ternary liquid mixtures.